DETERMINAN FAKTOR PENGEMBANGAN KARIR KARYAWAN: PENGALAMAN KERJA, TINGKAT PENDIDIKAN DAN KARAKTERISTIK INDIVIDU - Muhamad Irfan Priyono; Didin Hikmah Perkasa (LP2M Universitas Bina Bangsa, 2024)
Career development is one of the factors of work motivation. Research is important to do because it is a novelty study. Research involving determinant factors of career development including individual characteristic factors that are rarely researched. This study aims to determine the determinant factors that influence the career development of an employee, especially related to work experience, education level and individual characteristics at PT Cempaka Sinergy Realty (Building Management Division of Arandra Residence Apartment). The type of research used is quantitative research using a Linkert scale as a measurement tool. The population in this study were 52 employees of PT Cempaka Sinergy Realty (Arandra Residence Apartment Building Management Division), with a saturated sample model technique. Data analysis using SEM PLS equation modeling. The first stage maps the dimensions / indicators of each variable studied. The second stage tests the validity and reliability of each variable. The results showed that work experience has a positive and significant effect on employee career development, education level has a positive and significant effect on employee career development, and individual characteristics have a positive and significant effect on employee career development